Evolution of postural diversity in primates as reflected by the size and shape of the medial tibial facet of the talus. Issue 1 (14th February 2015) - Boyer, Doug M.; Yapuncich, Gabriel S.; Butler, Jared E.; Dunn, Rachel H.; Seiffert, Erik R.
ABSTRACT Objectives: Comprehensive quantification of the shape and proportions of the medial tibial facet (MTF) of the talus (=astragalus) has been lacking for Primates and their closest relatives. In this study, aspects of MTF form were quantified and employed to test hypotheses about their functional and phylogenetic significance. The following hypotheses influence perceptions of primate evolutionary history but are due for more rigorous assessment: 1) A relatively large MTF distinguishes "prosimians" (strepsirrhines and tarsiers) from anthropoids and non‐primate euarchontans; 2) the distinctive form of the "prosimian" MTF is a correlate of locomotor tendencies that emphasize use of vertical and small diameter supports in conjunction with inverted, abducted foot postures; and 3) the "prosimian" MTF form arose along the primate stem lineage and was present in the euprimate common ancestor. Methods: Three‐dimensional (3D) scanning was used to create scale digital models of tali (n = 378 specimens, 122 species) from which three types of variables capturing aspects of MTF form were computed: 1) MTF area relative to body mass and ectal facet area; 2) MTF shape (elliptical vs. non‐elliptical); and 3) MTF dorsal restriction on the talar body (i.e., extensive vs. minimal exposure of non‐articular area). Data were analyzed using both phylogenetic and traditional comparative methods including Phylogenetic Generalized Least Squares, Ordinary Least Squares, ANCOVA, ANOVA, and Bayesian Ancestral State Reconstruction (ASR). Results: Extant "prosimians" are generally distinct from anthropoids and non‐primate euarchontans in our quantitative representations of MTF form. MTF area (but not shape or dorsal restriction) correlates with fibular facet angle (FFa) of the talus, which has also been argued to reflect habitual pedal inversion. Among strepsirrhines, taxa that engage in grasp‐leaping more frequently/effectively appear to have a relatively larger MTF than less acrobatic taxa. Directional models of evolutionary change better describe the phylogenetic distribution of MTF variation than do other models. ASR shows 1) little change in the MTF along the primate stem, 2) independent evolution of relatively large and dorsoplantarly deep MTFs in basal haplorhines and strepsirrhines, and 3) re‐evolution of morphologies similar to non‐euprimates in anthropoids. Conclusions: Results support the hypothesis that differences in MTF form between anthropoids and "prosimians" reflect greater use of inverted foot postures and grasp‐leaping in the latter group. Although fossil "prosimians" do not have the extreme MTF dimensions that characterize many extant acrobatic leapers, these variables by themselves provide little additional behavioral resolution at the level of individual fossils due to strong phylogenetic signal. ASR suggests that some specialization for use of inverted foot postures (as required in a fine‐branch niche) and modifications for grasp‐leaping evolved independently in basal strepsirrhine and haplorhine lineages. Am J Phys Anthropol 157:134–177, 2015. © 2015 Wiley Periodicals, Inc.